Alcohol enhances the psychostimulant and conditioning effects of mephedrone in adolescent mice; postulation of unique roles of D3 receptors and BDNF in place preference acquisition. (9th October 2015) - Ciudad‐Roberts, Andrés; Camarasa, Jorge; Ciudad, Carlos J.; Pubill, David; Escubedo, Elena
Abstract : Background and Purpose: The psychostimulant mephedrone is often consumed in combination with alcohol (EtOH). This kind of drug consumption during adolescence is a matter of concern. Experimental Approach: We studied, in adolescent CD‐1 mice, whether EtOH could enhance the psychostimulant (locomotor acivity) and rewarding [conditioned place preference (CPP)] effects of mephedrone. We also determined the transcriptional changes associated with a conditioning treatment with these drugs. Key Results: Mephedrone (10 mg·kg −1 ) increased locomotor activity, which was further enhanced by 40% when combined with EtOH (1 g·kg −1 ). This enhancement was blocked by haloperidol. Furthermore, mephedrone (25 mg·kg −1 ) induced CPP, which increased by 70% when administered with a dose of EtOH that was not conditioning by itself (0.75 g·kg −1 ). There was enhanced expression of the D3 dopamine receptor mRNA ( Drd3 ) and Arpc5 in all drug‐treated groups. The D3 receptor antagonist SB‐277011A and the BDNF receptor antagonist ANA‐12 completely prevented CPP as well as the increases in Drd3 in all groups. Accordingly, increased expression of BDNF mRNA in medial prefrontal cortex was detected at 2 and 4 h after mephedrone administration. Conclusions and Implications: If translated to humans, the enhancement of mephedrone effects by ethanol could result in increased abuse liability. D3 receptors and BDNF play a key role in the establishment of CPP by mephedrone, although an accompanying increase in other synaptic plasticity‐related genes may also be necessary.